Challenges and opportunities for enhanced cognitive behaviour therapy (CBT-E) in light of COVID-19. (2020) - Murphy, Rebecca; Calugi, Simona; Cooper, Zafra; Dalle Grave, Riccardo
Abstract: In the past few weeks, coronavirus disease 2019 (COVID-19) has dramatically expanded across the world. To limit the spread of COVID-19 and its negative consequences, many countries have applied strict social distancing rules. In this dramatic situation, people with eating disorders are at risk of their disorder becoming more severe or relapsing. The risk comes from multiple sources including fears of infection and the effects of social isolation, as well as the limited availability of adequate psychological and psychiatric treatments. A potential practical solution to address some of these problems is to deliver enhanced cognitive behaviour therapy (CBT-E), an evidence-based treatment for all eating disorders, remotely. In this guidance we address three main topics. First, we suggest that CBT-E is suitable for remote delivery and we consider the challenges and advantages of delivering it in this way. Second, we discuss new problems that patients with eating disorders may face in this period. We also highlight potential opportunities for adapting some aspects of CBT-E to address them. Finally, we provide guidelines about how to adapt the various stages, strategies and procedures of CBT-E for teletherapy use in the particular circumstances of COVID-19. Key learning aims: (1) To appreciate that CBT-E is suitable for remote delivery, and to consider the main challenges and potential advantages of this way of working. (2) To identify and discuss the additional eating disorder-related problems that may arise as a result of COVID-19, as well as potential opportunities for adapting some aspects of CBT-E to address them. (3) To learn how to adapt CBT-E for remote delivery to address the consequences of COVID-19. Specifically, to consider adaptations to the assessment and preparation phase, the four stages of treatment and its use with underweight patients and adolescents.